A modified Delphi exercise to determine the extent of consensus with OMERACT outcome domains for studies of acute and chronic gout. Issue 6 (29th November 2007) - Taylor, W J; Schumacher, H R; Baraf, H S B; Chapman, P; Stamp, L; Doherty, M; McQueen, F; Dalbeth, N; Schlesinger, N; Furst, D E; Mellado, J Vazquez; Becker, M A; et al.
Abstract : Objectives: To reach consensus with recommendations made by an OMERACT Special Interest Group (SIG). Methods: Rheumatologists and industry representatives interested in gout rated and clarified, in three iterations, the importance of domains proposed by the OMERACT SIG for use in acute and chronic gout intervention studies. Consensus was defined as a value of less than 1 of the UCLA/RAND disagreement index. Results: There were 33 respondents (61% response rate); all agreed the initial items were necessary, except "total body urate pool". Additional domains were suggested and clarification sought for defining "joint inflammation" and "musculoskeletal function". Items that demonstrated no clear decision were re-rated in the final iteration. There were six highly rated items (rating 1–2) with four slightly lower rating items (rating 3) for acute gout; and 11 highly rated items with eight slightly lower ratings for chronic gout. Conclusions: Consensus is that the following domains be considered mandatory for acute gout studies: pain, joint swelling, joint tenderness, patient global, physician global, functional disability; and for chronic gout studies: serum urate, gout flares, tophus regression, health-related quality of life, functional disability, pain, patient global, physician global, work disability and joint inflammation. Several additional domains were considered discretionary.